Single and Dual Targeting of Mutant EGFR with an Allosteric Inhibitor - Ciric To; Jaebong Jang; Ting Chen; Eunyoung Park; Mierzhati Mushajiang; Dries J.H. De Clercq; Man Xu; Stephen Wang; Michael D. Cameron; David E. Heppner; Bo Hee Shin; Thomas W. Gero; et al. (2019)
Allosteric kinase inhibitors offer a potentially complementary therapeutic strategy to ATP-competitive kinase inhibitors due to their distinct sites of target binding. In this study, we identify and study a mutant-selective EGFR allosteric inhibitor, JBJ-04-125-02, which as a single agent can inhibit cell proliferation and EGFRL858R/T790M/C797S signaling in vitro and in vivo. However, increased EGFR dimer formation limits treatment efficacy and leads to drug resistance. Remarkably, osimertinib, an ATP-competitive covalent EGFR inhibitor, uniquely and significantly enhances the binding of JBJ-04-125-02 for mutant EGFR. The combination of osimertinib and JBJ-04-125-02 results in an increase in apoptosis, a more effective inhibition of cellular growth, and an increased efficacy in vitro and in vivo compared with either single agent alone. Collectively, our findings suggest that the combination of a covalent mutant-selective ATP-competitive inhibitor and an allosteric EGFR inhibitor may be an effective therapeutic approach for patients with EGFR-mutant lung cancer. SIGNIFICANCE: The clinical efficacy of EGFR tyrosine kinase inhibitors (TKI) in EGFR-mutant lung cancer is limited by acquired drug resistance, thus highlighting the need for alternative strategies to inhibit EGFR. Here, we identify a mutant EGFR allosteric inhibitor that is effective as a single agent and in combination with the EGFR TKI osimertinib.This article is highlighted in the In This Issue feature, p. 813.